Using educational game apps in improving students mathematics’ learning: an exploratory study on third grader at-risk classroom at primary school in Selangor, Malaysia - Mohd Hashim, Syaza Hazirah; Hashim, Sulaiman; Tunku Ahmad, Tunku Badariah (Contemporary Research Center CRC Publications, 2019)
Researches on the effectiveness of technology used in learning had shed different light on its affordances in line with the 21st century students. With the student getting savvy by days, this call for newer and relevant approaches towards the use of technology in the classroom. The use of technology should be considered as a tool to meet the demanding of a niche group such as the special need and at-risk learner who need more comprehensive and inclusive tutoring. To fill the gap, this paper explored the use of game apps in facilitating the at-risk third grader's learning at four schools in one districts in Malaysia. Pre and post-test showed that the used of mathematics-based app improved student mental calculation and reduced time needed to complete the exercise. Much deeper study on the effectiveness use of technology in the at-risk classroom should be conducted in the future.